Availability of essential medicines in primary health care of the Brazilian Unified Health System - Nascimento, Renata Cristina Rezende Macedo do; Álvares, Juliana; Guerra Junior, Augusto Afonso; Gomes, Isabel Cristina; Costa, Ediná Alves; Leite, Silvana Nair; Costa, Karen Sarmento; Soeiro, Orlando Mario; Guibu, Ione Aquemi; Karnikowski, Margô Gomes de Oliveira; Acurcio, Francisco de Assis (Revista de Saúde Pública, 2017)
OBJECTIVE: To characterize the availability of tracer medicines in pharmaceutical services in primary health care of the Brazilian Unified Health System (SUS). METHODS: This is a cross-sectional and evaluative study, part of the Pesquisa Nacional Sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015). To analyze the availability of medicines, we verified 50 items selected from the Relação Nacional de Medicamentos Essenciais (Rename – National List of Essential Medicines) of 2012. Observation scripts were applied to medicine dispensing services in the primary health care. Interviews were carried out with patients, health care professionals, and public managers, using semi-structured questionnaires. The availability index was presented as the percentage of health units where the medicines were available. For statistical analysis, absolute, relative, and mean frequencies were presented (with 95% confidence intervals). The comparison of groups was carried out by Pearson Chi-square tests or variance analysis, when needed. RESULTS: One thousand, one hundred, and seventy-five observation scripts were filled in a national representative sample composed by 273 cities. Statistically significant differences were observed regarding the type of unit, infrastructure, and presence of a pharmacist between regions of Brazil. The average availability of tracer medicines in primary health care was 52.9%, with differences between regions and sampling strata. This index increased to 62.5% when phytotherapic medicines were excluded. We found limited availability of medicines for treatment of chronic and epidemiological diseases, such as tuberculosis and congenital syphilis. CONCLUSIONS: The low availability of essential medicines purchased centrally by the Brazilian Ministry of Health indicates deficiencies in supply chain management. The different views on the availability of tracer medicines in SUS confirm the general availability verified in this study. Among patients, about 60% said they obtain medicines in SUS units, data consistent with the lack of medicines reported by medicine dispensers and in line with physicians’ evaluations